Comment on "Photodegradation of sulfathiazole under simulated sunlight: Kinetics, photo-induced structural rearrangement, and antimicrobial activities of photoproducts" by Niu et al. [Water Research 124 2017 576–583]. (15th March 2018) - Hain, Ethan; Wammer, Kristine H.; Blaney, Lee
Abstract: Recent efforts have employed antimicrobial susceptibility assays to describe the residual antimicrobial activity of antibiotics and their transformation products in a variety of environmental processes. Some authors have evaluated the results of these assays using the minimum inhibitory concentration (MIC); however, this approach has fundamental weaknesses. To highlight best practices, this comment describes the advantages of using dose-response curves to calculate the half maximal inhibitory concentration (IC50 ) and the potential impacts of growth media on the antimicrobial activity of sulfonamide antibiotics. Highlights: Disadvantages of MIC-based analysis of residual antimicrobial activity. Comparison of IC50 values is best practice for antimicrobial activity measurement. Growth media may interfere with antimicrobial activity of sulfonamides.